2009
DOI: 10.7589/0090-3558-45.3.637
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Shell Disease in Map Turtles (Graptemys Spp.)

Abstract: ABSTRACT:Nineteen map turtles (Graptemys spp.) maintained under natural conditions were investigated because of chronic shell abnormalities. Animals were evaluated using a novel shell scoring system that divided the 54 scutes into six regions, with each region scored for lesion extent and severity, and summated to produce a total shell disease score (TSDS). Complete blood counts and various biochemistry analytes (total protein, albumin, globulin, urea, uric acid, 25-hydroxycholecalciferol, phosphorus, and ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
6
22
1
3
Order By: Relevance
“…E. tarda and C. freundii have been isolated from clinical samples of soft-shelled turtles with fulminant septicaemia (Hu et al 2010). In agreement with previous studies (Kohler 2006;HernandezDivers et al 2009;Hu et al 2010;Chen et al 2013a;Chen et al 2013b), we identified aeromonads and enteric bacteria as the major pathogens associated with septicaemia and skin/shell diseases in softshelled turtles. However, to the best of our knowledge, there is no information regarding infection with W. chitiniclastica and Comamonas spp.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…E. tarda and C. freundii have been isolated from clinical samples of soft-shelled turtles with fulminant septicaemia (Hu et al 2010). In agreement with previous studies (Kohler 2006;HernandezDivers et al 2009;Hu et al 2010;Chen et al 2013a;Chen et al 2013b), we identified aeromonads and enteric bacteria as the major pathogens associated with septicaemia and skin/shell diseases in softshelled turtles. However, to the best of our knowledge, there is no information regarding infection with W. chitiniclastica and Comamonas spp.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, most of the identified bacterial species have been reported as infectious agents responsible for septicaemia in chelonia (Oros et al 2005;Hernandez-Divers et al 2009;Hu et al 2010). C. freundii is known to be the aetiological agent of septicaemic cutaneous ulcerative disease (SCUD), which is accompanied by liver necrosis (Kohler 2006).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Aeromonas and Pseudomonas spp. have been isolated from turtles with pneumonia, and many other infections in turtles with bacterial aetiologies have been described (McArthur 2004;Kohler 2006;Hernandez-Divers et al 2009;Chen et al 2013;Chung et al 2017).…”
mentioning
confidence: 99%